Heart rate variability: effect of exercise intensity on postexercise response - James, D. V. B.; Munson, S. C.; Maldonado-Martin, S.; de Ste Croix, M. B. A. (Research Quarterly for Exercise and Sport, 2012)
The purpose of the present study was to investigate the influence of two exercise intensities (moderate and severe) on heart rate variability (HRV) response in 16 runners 1 hr prior to (-1 hr) and at +1 hr, +24 hr, +48 hr, and +72 hr following each exercise session. Time domain indexes and a high frequency component showed a significant decrease (p < .001) between -1 hr and +1 hr for severe intensity. The low frequency component in normalized units significantly increased (p <.01) for severe intensity at +1 hr. Only severe exercise elicited a change in HRV outcomes postexercise, resulting in a reduction in the parasympathetic influence on the heart at +1 hr; however, values returned to baseline levels by +24 hr.